2014
DOI: 10.1155/2014/274949
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Based Multiple Choice Question Generation

Abstract: With recent advancements in Semantic Web technologies, a new trend in MCQ item generation has emerged through the use of ontologies. Ontologies are knowledge representation structures that formally describe entities in a domain and their relationships, thus enabling automated inference and reasoning. Ontology-based MCQ item generation is still in its infancy, but substantial research efforts are being made in the field. However, the applicability of these models for use in an educational setting has not been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…For a detailed review of the related literature, the interested reader is referred to [2]. A number of ontology-based question generation approaches have been proposed [3,6,7,12,15,19,20]. For example, Zitko et al [19] proposed templates and algorithms for the automatic generation of objective questions from ontologies.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For a detailed review of the related literature, the interested reader is referred to [2]. A number of ontology-based question generation approaches have been proposed [3,6,7,12,15,19,20]. For example, Zitko et al [19] proposed templates and algorithms for the automatic generation of objective questions from ontologies.…”
Section: Related Workmentioning
confidence: 99%
“…MCQs are, however, rather difficult to design [9], regardless of whether we design them by hand or automatically: in addition to a good question 2 and a correct answer, 3 we need to generate suitable distractors, i.e., reasonable yet incorrect alternative answers. To generate a good set of MCQs, i.e., an exam, we need to control the difficulty of MCQs: a good exam has to have questions from a range of difficulties so that it faithfully assesses students' understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach in this paper is an effort in this direction. We observed that most of the existing MCQ generation techniques [7] randomly select instances which do not belong to the class of the correct answer as distractors. The incorrectness of the distractors cannot be ensured by this random selection method, which in turn made it necessary to manually check the correctness of the question items before making use of them.…”
Section: Movieda(braveheart)mentioning
confidence: 99%
“…Recently, a handful of studies [3][4][5][6][7][8][9] explored the use of structured domain knowledge in the form of description logic based ontologies to automatically generate MCQs. This would enable online assessment systems to utilize existing knowledge bases for the assessment of learner's knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%